Pengaruh Eksplorasi Karir dan Parental Support terhadap Career Adaptability Siswa di SMK Teuku Umar Semarang - Puspa Ndari; Indrajati Kunwijaya (Program Studi Bimbingan dan Konseling FKIP UMSU, 2026)
This study aims to examine the effect of career exploration and parental support on career adaptability among students at SMK Teuku Umar Semarang. Career adaptability is a critical competency for vocational students in facing the increasingly complex demands of the world of work, yet empirical studies integrating career exploration and parental support simultaneously as predictors in the context of Indonesian vocational education remain limited. This study employed a quantitative approach with a correlational non-experimental design. The population consisted of 626 students from grades X, XI, and XII, with a sample of 244 students selected through proportionate stratified random sampling. Data were collected using the Career Adapt-Abilities Scale–Short Form (CAAS-SF), Career Exploration Survey (CES), and Career-Related Parental Support Scale (CRPSS), and analyzed using multiple linear regression. The results show that career exploration has a significant effect on career adaptability (sig. = 0.000), and parental support also has a significant effect on career adaptability (sig. = 0.012). Simultaneously, both variables significantly influence career adaptability, contributing 65.5% to the variance explained (Adjusted R² = 0.655). These findings confirm that students' career adaptability is shaped by internal factors in the form of career exploration and external factors in the form of parental support. Therefore, improving career adaptability requires strengthening career exploration programs in schools alongside active parental involvement in students' career planning processes.